Ameliorative effect of ethanolic extract of Limnophila rugosa (Scrophulariaceae) in paracetamol- and carbon tetrachloride-induced hepatotoxicity in rats - R. N. Hota; B. K. Nanda; B. R. Behera; A. Bose (SpringerOpen, 2022)
Abstract Background Limnophila rugosa (Scrophulariaceae) is a perennial aquatic plant used as a diuretic and digestive tonic as well as in the treatment of diarrhea, dysentery, dyspepsia and urinary ailments. Genus Limnophila has been reported as hepatoprotective. The present study was undertaken to evaluate the hepatoprotective activity of the ethanolic extract of L. rugosa aerial part in paracetamol- and carbon tetrachloride-induced (CCl4) hepatotoxicity in albino Wistar rats. Ethanolic extract was subjected to high-performance liquid chromatography (HPLC) analysis for the estimation of phenolic and flavonoid compounds and gas chromatography-mass spectrometry (GC-MS) analysis for phytochemical analysis. The in vitro antioxidant activity was carried out by 2,2-diphenyl-1-picrylhydrazyl, nitric oxide radical and hydrogen peroxide assay. Hepatoprotective potential of L. rugosa was studied in paracetamol (750 mg/mg)- and CCl4 (1.25 ml/kg)-induced liver damage in albino rats at dose 200 and 300 mg/kg using silymarin (100 mg/kg) as standard. Lipid peroxidation, superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH) were determined in liver tissue homogenate. Serum biochemical and histopathological examination was performed. Molecular docking analysis was performed to understand the molecular mechanism of hepatoprotective activity. Results HPLC analysis revealed predominance of rutin. GC-MS analysis revealed camphor as principal component. Ethanolic extract exhibited significant concentration-dependent scavenging efficacy. The altered biochemical chemical parameters: aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, bilirubin, cholesterol, albumin, globulin and total protein, were significantly improved at 200 and 300 mg/kg in experimental rats. Extract signified hepatoprotective by decreasing lipid peroxidation and upregulating SOD, CAT and GSH. The findings were well supported by histological analysis. 2-Butyl-2, 7-octadien-1-ol (-5.8) and camphor (-4.8) gave the highest docking score on the transforming growth factor-β1. Conclusions The ameliorative effect of L. rugosa in the rat model of hepatotoxicity could be attributed to its antioxidant potential and bioactive principles such as betulin, 5-hydroxy-6,7,4'-trimethoxyflavone (salvigenin), betulinic acid, ursolic acid, 3-octanol, acetophenone, anisylacetone, caryophyllene, cis-anethole and the compounds camphor and 2-butyl-2,7-octadien-1-ol identified from GC-MS analysis.